Deformation of the Cooling Vessel's Shell - Katarina Pisačić; Mario Pintarić (Tehnički Glasnik)
This paper will present the procedure for calculating the internal volume obtained by deforming the outer shell of the cooling vessel. A nonlinear finite element analysis was conducted using the Ansys software. The material behavior when it transitions into the plastic deformation region was defined, and the deformed shape resulting from the plastic deformation of the outer shell of the cooling vessel was obtained. The volume of the deformed shape was determined with several simplifications: the profile of the outer shell was simplified into a circular arc, and the parameters of the circle were calculated. The formula for the volume of a rotational body was used to calculate the volume.